2020
DOI: 10.1101/2020.01.29.924712
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A simple model for glioma grading based on texture analysis applied to conventional brain MRI

Abstract: 11Accuracy of glioma grading is fundamental for the diagnosis, treatment planning and 12 prognosis of patients. The purpose of this work was to develop a low cost and easy to 13 implement classification model which distinguishes low grade gliomas (LGGs) from high 14 grade gliomas (HGGs), through texture analysis applied to conventional brain MRI. 15Different combinations between MRI contrasts (T 1Gd and T 2 ) and one segmented 16 glioma region (necrotic and non-enhancing tumor core (NCR/NET)) were studied. 17 … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 47 publications
1
4
0
Order By: Relevance
“…12 A recent study used texture analysis with different combinations of MRI images on post-contrast T1-weighted images and T2-weighted images and found a sensitivity of 94% to differentiate low-grade gliomas from high-grade gliomas. 30 In our study, the maximum ADC of 2.026 or less in tumour ROI had a sensitivity of 95% to differentiate GBM from PCNSL and the ADC mean of 0.943 or less in the tumour region had a specificity of 91.2%. The sensitivity and specificity in our study were comparable to previous studies, 9,12,14 although there is deference in the cut-off values among the studies, which is likely to be due to the differences in MRI machine, software used, ROI selection technique and image analysis tools.…”
Section: Discussionsupporting
confidence: 45%
“…12 A recent study used texture analysis with different combinations of MRI images on post-contrast T1-weighted images and T2-weighted images and found a sensitivity of 94% to differentiate low-grade gliomas from high-grade gliomas. 30 In our study, the maximum ADC of 2.026 or less in tumour ROI had a sensitivity of 95% to differentiate GBM from PCNSL and the ADC mean of 0.943 or less in the tumour region had a specificity of 91.2%. The sensitivity and specificity in our study were comparable to previous studies, 9,12,14 although there is deference in the cut-off values among the studies, which is likely to be due to the differences in MRI machine, software used, ROI selection technique and image analysis tools.…”
Section: Discussionsupporting
confidence: 45%
“…Texture analysis is a postprocessing method for extracting information by quantifying the spatial distribution of pixels or voxels with different gray intensities and counting the variables, that is, calculating and extracting texture features based on the texture matrix of images. This is one of the more commonly used methods in radiomics research [ 7 , 8 ]. The first-order feature describes the gray distribution of individual pixel values in ROIs.…”
Section: Discussionmentioning
confidence: 99%
“…Suárez-García et al from texture features obtained from the gray level size zone matrix calculated that the best model reached a sensitivity, specificity and accuracy of 94.12%, 88.24% and 91.18% respectively, providing a simple, low cost, easy to implement, reproducible and highly accurate glioma classifier, accessible to populations with reduced economic and scientific resources. 12 Similarly, Nakamoto et al concluded that the grade III and IV glioma scan be accurately and easily predicted by radiomic analysis of contrast-enhanced T1 and T2 weighted images. 39 Addition of advanced sequences would have enriched this study by allowing assessment of their impact on the predictive accuracy of conventional MRI, but cost constraints limited it to conventional sequences of MRI only.…”
Section: Overall Correlation Of All Criteria Combined Togethermentioning
confidence: 98%